PERFORMANCES OF VILLAGE CHICKEN FOLLOWING CROSS BREEDING WITH DIFFERENT BREEDS OF CHICKEN - Takdir Saili; Rusli Badaruddin; La Ode Nafiu (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
The performances of village chicken in South-east Sulawesi, Indonesia were typically small and light weight, and low productivity of both egg and meat. However, they more resistant to disease compared to other breed of chicken such as commercial broiler or layer. Therefore, in this research the more productive breed of cocks were used. The objective of this research was to improve productivity of the village chicken using different breeds of cock. Bangkok-crossed breed chicken, commercial broiler and village chicken were used to mate the hen of village chicken using artificial insemination. Variables measured were egg fertility, egg hatchability, and day old chick weight of village chicken crossed by different breeds. Duncan multiple range test was applied to compare the averages of each data. The results showed that the higher egg fertility and hatchability were obtained when crossing the hen of village chicken and bangkok-crossed breed cocks, although no statistical differences was showed between breeds of cock. The average of day old chick weight was also higher in a group of village chicken hen crossed by bangkok-crossed breed cocks compare to other breeds, but no significant differences was showed. It was concluded that the bangkok-crossed breed cocks tended to be a good candidate for increasing the productivity of village chicken.